Cost-effectiveness of a proportionate universal offer of free exercise: Leeds Let’s Get Active - Candio, P; Meads, D; Hill, AJ; Bojke, L (Oxford University Press, 2020)
Background The purpose of this paper is to assess the cost-effectiveness of a proportionate universal programme to reduce physical inactivity (Leeds Let us Get Active (LLGA)) in adults.